Peculiarities of Transfer Pricing Supervision in Uncontrolled Transactions - E. Sh. Saliakhutdinov (Теоретическая и прикладная юриспруденция)
The aim of this article is to scrutinize the authority of tax agencies concerning the transfer pricing supervision in uncontrolled transactions among related parties. The interpretation of tax laws by the Russian Federal Tax Service has significantly broadened the supervision capabilities of tax agencies over taxpayer transactions initially not meant for scrutiny, resulting in ambiguity and inconsistency in legal proceedings. The article provides an analysis of the legal framework, methodology, and procedures for tax control of prices in uncontrolled transactions, as well as examines the concept of “multiple price deviations” and taxpayer defense strategies. The methodological basis of the article includes both general scientific and specialized scientific methods. In particular, the author employs analysis, synthesis, formal legal, and historical-legal methods. The findings suggest disparities in the treatment of taxpayers in transfer pricing supervision due to the absence of specific safeguards outlined in Section V.1 of the Tax Code of the Russian Federation. Consequently, the author advocates for an extension of transfer pricing laws to encompass all taxpayers, thereby ensuring parity in rights and protections while mitigating arbitrary actions and uncertainties by tax agencies, thereby fostering a more equitable and transparent tax supervision system.